“Case Report : Early Congenital Syphilis” - Herjuni Oematan; Ayu Cyntia Tanto (Journal of Comprehensive Science, 2026)
Congenital syphilis is a serious infection transmitted from mother to fetus, causing multisystem complications in infants. A 5-month-old male infant presented with skin desquamation, alopecia, shortness of breath, and cough. Physical examination revealed alopecia, saddle nose deformity, and extensive skin lesions. Serological testing confirmed early congenital syphilis with a positive VDRL titer of 1:32. The patient also suffered from severe anemia (Hb 4.9 g/dL), thrombocytopenia, and pneumonia. Despite receiving treatment with benzathine penicillin, antibiotics, and blood transfusion, the patient’s condition worsened, leading to death six days after hospitalization. This case highlights the severe manifestations of early congenital syphilis and the importance of early diagnosis and timely treatment. Delays in prenatal screening and limited healthcare access contributed to the delayed diagnosis. Although standard treatment was administered, the patient’s prognosis was poor due to secondary infections and comorbidities. Prenatal screening and public health education are crucial in reducing congenital syphilis cases. Early detection and management are essential to improving outcomes and reducing mortality in affected infants.